Alternative Runx1 promoter usage in mouse developmental hematopoiesis. - Bee, T; Liddiard, K; Swiers, G; Bickley, SR; Vink, C; Jarratt, A; Hughes, J; Medvinsky, A; de Bruijn, M (2009)
The interest in stem cell based therapies has emphasized the importance of understanding the cellular and molecular mechanisms by which stem cells are generated in ontogeny and maintained throughout adult life. Hematopoietic stem cells (HSCs) are first found in clusters of hematopoietic cells budding from the luminal wall of the major arteries in the developing mammalian embryo. The transcription factor Runx1 is critical for their generation and is specifically expressed at sites of HSC generation, prior to their formation. To understand better the transcriptional hierarchies that converge on Runx1 during HSC emergence, we have initiated studies into its transcriptional regulation. Here we systematically analyzed Runx1 P1 and P2 alternative promoter usage in hematopoietic sites and in sorted cell populations during mouse hematopoietic development. Our results indicate that Runx1 expression in primitive erythrocytes is largely P2-derived, whilst in definitive hematopoietic stem and/or progenitor cells from the yolk sac or AGM and vitelline and umbilical arteries both the distal P1 and proximal P2 promoters are active. After cells have migrated to the fetal liver, the P1 gradually becomes the main hematopoietic promoter and remains this into adulthood. In addition, we identified a novel P2-derived Runx1 isoform.